The wedding heard 'round the world : America's first gay marriage - McConnell, Michael, 1942-; Baker, Jack, 1942- (University of Minnesota Press, 2016)
"On September 3, 1971, Michael McConnell and Jack Baker exchanged vows in the first legal same-sex wedding in the United States. Their remarkable story is told here for the first time--a unique account of the passion and energy of the gay liberation movement in the sixties and seventies. At the dawn of the modern gay movement (while New York's Stonewall riots and San Francisco's emerging political activism bloomed), these two young men insisted on making their commitment a legal reality. They were already crusaders for gay rights: Jack had twice been elected the University of Minnesota's student president--the first openly gay university student president in the country, an election reported by Walter Cronkite on network TV news. They were featured in LOOK magazine's special issue about the American family and received letters of support from around the world. The couple navigated complex procedures to obtain a state-issued marriage license. Their ceremony was conducted by a Methodist minister in a friend's tiny Minneapolis apartment. Wearing matching white pantsuits, exchanging custom-designed rings, and sharing a tiered wedding cake, Michael and Jack celebrated their historic marriage. After reciting their vows, they sealed their promise to love and honor each other with a kiss and a signed marriage certificate. Repercussions were immediate: Michael's job offer at the University of Minnesota was rescinded, leading him to wage a battle against job discrimination with the help of the Minnesota Civil Liberties Union. The couple eventually reached the U.S. Supreme Court with two precedent-setting cases. Michael and Jack have retired from the public spotlight, but after four decades their marriage is still their joy and comfort. Living quietly in a Minneapolis bungalow, they exemplify a contemporary version of the American dream. Only now, with marriage equality in the headlines and the Supreme Court decision to make love the law of the land, are they willing to tell the entire story of their groundbreaking experiences. TIME magazine listed the twenty-five most influential marriages of all time and included Michael and Jack, and they were recently profiled in a cover story in the Sunday New York Times. Their long campaign for marriage equality and insistence on equal rights for all citizens is a model for advocates of social justice and an inspiration for everyone who struggles for acceptance in a less-than-equal world."--